Predicting students' performance through techniques in study skills : a multivariate discriminant analysis approach / Shukri Shamsuddin, Noor Izah Ismail and Wan Haslina Wan Hussin - Shamsuddin, Shukri; Ismail, Noor Izah; Wan Hussin, Wan Haslina (Institute of Research, Development and Commercialization (IRDC), 2007)
This paper investigates some of the study skills techniques practised by students in UiTM Johor campus. The multivariate discriminant analysis approach was used to analyse the data. The discussion focuses on to what extent these study skills techniques could be used to predict the academic performance ofstudents. This paper also examines whether there is a significant difference in study skills techniques practised by male and female students, by students of different secondary school backgrounds, and by students of different academic performances. It is hoped that this paper would shed some light on the effectiveness of the study skills program introduced to part one students upon entry into UiTM Johor.